EFFECT OF PATIENT'S PERSONAL CHARACTER ON PREVENTION OF TRANSMISSION OF PULMONARY TB - Herdianti, Herdianti; Entianopa, Entianopa; Sugiarto, Sugiarto (Institute of Topical Disease Universitas Airlangga, 2020)
Tuberculosis (TB) is an infectious disease that is still a problem for health in the world, caused by Mycobacterium tuberculosis. Muaro Jambi showed second ranks of TB patients number in Jambi Province. Based on the available data, the biggest positive TB patients were in the Muara Kumpeh Health Center working area which was 54 people (2016) and 68 people (2017). The purpose of this study was to determine the relationship and risk of Self Efficacy and Interpersonal Relations to the prevention of pulmonary TB transmission in the Muara Kumpeh Health Center in Muaro Jambi District in 2018. This research is a quantitative research with Cross Sectional Study research design. The sample of this study was 68 people interviewed using questionnaire with the Total Sampling. The research was carried out in the work area of Muara Kumpeh Health Center in April-August 2018. The data was collected then analyzed in univariate and bivariate. A total of 37% of respondents were adults (26-45 years), 53% of male patients and 52% of respondents were treated by their spouses during illness. There was a significant relationship (p-value = 0.011) between self efficacy and TB transmission prevention behavior and low self efficacy at 5.14 times the risk of transmitting pulmonary TB compared to high self efficacy. With high self confidence from respondents can provide good motivation for their recovery. There was no significant relationship (p-value = 0.104) between interpersonal relationships with TB transmission prevention behaviors and interpersonal relationships not risk factors for preventing TB transmission behavior. This could be due to not too much percentage difference between respondents who have low and high interpersonal relationships. Besides that, the knowledge factor of the patient's family can also be confounding on this variable. Low self efficacy has a risk of 5.14 times transmitting TB and this is statistically significant. It is better to do more routine care of the patient's family so that it can improve self efficacy and interpersonal relationships of the patient.